O abuso decorrente da violação à finalidade econômica do direito - Boraschi, Reginaldo (2013)
Although the current Civil Code has been concerned with the definition of the institute to which the doctrine and jurisprudence termed called "abuse of rights" (Art. 187, CC), a reflection of the subject, and even more solutions and reach of Legal Writing that matter can assume achieve practical importance can be a new theme in the lives of our courts, because, at present, little has been addressing the abuse of the right of economic purpose. On this issue, perhaps even bringing the legal sciences definitions and concepts of economics entail a move away from the operator of the subject. The institute treated in this research is economic, but above all, legal. The economy is fueled by the malleability of the facts that surround it, more adapted to today's, the right, however, aims to lend strength to the same facts then used by economists, imposing, even against the will of individual liability, facet with which the economy is not identified. Open the way for the recovery of critical legal concept, we must think and reflect on the practical application of the institute, without neglecting the formula adopted by their inspirational. The effectiveness of this right, moreover, is consistent with the line of research adopted by the Program of Postgraduate Studies in Law from the Pontifical Catholic University of São Paulo. In this trajectory, we intend to discuss the main characteristics of abuse of rights, with emphasis on sociological and legal criteria for the institute. It seems the work of past criticism of the doctrine that denied the existence of abuse of rights, based mainly on the claim that the right stops where abuse begins, or in the absence of subjective rights. Abuser does not act without right. This right, however, is not unlimited, boundless. The system handles legal limit you when used contrary to the purposes for which it was designed. The abuse of the law, so care is an autonomous institute legal standing beside many other known and already sedimented in universal culture. The criterion defining the abuse of law, although made a speech about their elementary, according to the guidelines outlined by Article 187 of the current Brazilian Civil Code, the search for effective expression "economic purpose of the law" is the driving force behind this research. Your choice, by the way, is due exactly to the fact that the doctrine is poorly treated and even less in the case of the Courts. In this institute undeniable importance, relegate it to disuse for lack of criteria necessary for its use is something with which we can not agree